Kinerja Badan Jaminan Sosial Dan Kepuasan Pelanggan - Elsa Triandhani Putri; Hero Priono; Endah Susilowati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2017)
The purpose of this research is to test the quality of service and company capability through the customer satisfaction and company performance of Indonesia social security agency of human resource ( BPJS Ketenagakerjaan). This is quantitative research with survey method approach. It was population 1.011 people and distributed 91 questionnaires for BPJS Ketenagakerjaan Jember branch. Partial Least Square (PLS) software used to test the hyphotesis.The research found that service quality variable has effect through the customer satisfaction but does not have any effect for the company performance. Company capability variable affects the customer satisfaction and company performance.